Identification of dopamine- and serotonin-related genes modulated by bisphenol A in the prefrontal cortex of male rats. (November 2015) - Castro, Beatriz; Sánchez, Pilar; Miranda, María T.; Torres, Jesús M.; Ortega, Esperanza
Graphical abstract: Highlights: We assessed neurotoxicity of BPA in relation to precortical DA and 5-HT systems. Perinatal BPA exposure affected gene transcription in juvenile and adult male rats. BPA reduced the transcripts of precortical DA receptors in juvenile rats. BPA produced permanent alterations in Gdnf transcript levels. BPA reduced Tph2 and increased Th transcription in adult rats. Abstract: There is concern that exposure of embryos and/or infants to bisphenol A (BPA) may lead to neurological and behavioral disorders with unknown prefrontal cortex (PFC) involvement. Critical PFC functions are modulated by dopamine (DA) and serotonin (5-HT) systems, whose alterations have been associated with psychopathologies that may appear in youth and/or adulthood. This study aims to determine in the PFC of male rats exposed to a low dose of BPA (10 μg kg −1 d −1 ) from gestational day 12 (GD12) to postnatal day 21 (PND21): (i) DA- and 5-HT-related genes modulated by BPA at the juvenile stage (PND21); (ii) reversible and irreversible transcriptional effects; (iii) long-term consequences (effects in adult rats, PND90). In juvenile rats, BPA altered significantly the transcription of 12 out of the 84 genes analyzed using PCR-array techniques. Interestingly, transcript levels of the neurotrophic factor Gdnf were decrease by BPA in both juvenile and adult rats. At adulthood, disruptions in genes encoding rate-limiting enzymes for DA and 5-HT synthesis emerged. Overall, the results indicate that early-life exposure to BPA has consequences on DA and 5-HT systems in both juvenile- and adult-life stages. Additionally, we reveal molecular targets that could provide the foundation for future BPA neurotoxicity studies.